KARAKTERISTIK TES PRESTASI BELAJAR BERDASARKAN PENDEKATAN KLASIK DAN ITEM RESPONSE THEORY - Anak Agung Purwa Antara; Ni Made Serma Wati (Widyadari : Jurnal Pendidikan, 2021)
This research is empirical study in order to determine (1) the characteristics of achievement test which analyzed with classical approach, (2) the characteristics of achievement test which analyzed with Item Response Theory (IRT) approach and, (3) the comparison of slope that analyzed with classical and IRT approaches. This research was conducted in an elementary school in Tabanan with data retrieval using stratified random sampling technique. Characteristics of the test analyzed using Parscale Program (Muraki & Bock, 1977) with Marginal Maximum likelihood estimation. The results of the analyzed based on the classical approach shows that the average value of coefficient Pearson correlation 0.373 and the average of coefficient Polyserial correlation 0.460 more than 0.2 That means the general tests that arranged have good slope.. The results of analysis IRT approach indicated that the minimum value of probability 0.198 (greater than 0.05), which means fit with the model. The mean of slope 0.644, greater than 0.2. That means the tests have good slope. Similarly, the value of location of the test -.0.430, that means the tests have moderate level of difficulty. Analysis of test with IRT approach have an average slope greater than tests that analyze with classical approach. That means the analysis test with IRT approach more careful in distinguishing abilities of students with one another.